Zizyphus Mauritiana (Indian Jujube/Beri Spikes) of Bikaner, Rajasthan of India- An Anti-Cancerous Drug Formulation for Blood Cancer with Validated IC50- Calibration via FTIR, FESEM EDAX (AYUSHDHARA, 2023)
In order to analyse the bioactive constituents of spikes of Zizyphus Mauritiana/ Beri spikes of Bikaner, Rajasthan, Fourier Transform Infrared Spectroscopy (FTIR) and added Field Emission Scanning Electron Microscope with Energy Dispersive X-ray analysis (FESEM-EDAX) were carried out initially. The authors too demonstrated Cell line studies via MTT Assay for MOLT4 (Blood cancer) in different concentrations and found Beri spikes as toxic with Validated IC50 via Graph Prism Software. Concluded by the result, phytochemicals present in the spikes reflects it as bioactive compound which may act as antimicrobial, anti-cancerous, antiviral, and anti-inflammatory agents. On an all, Indian Jujube is all set to form a traditional medicine because of the effects it got via cell death when experimented for in-vitro trials on Blood Cancer cells.